Deciphering the benefits and intensity levels of primary metabolites from Allium macrostemon Bunge and Allium chinense G. Don - Zifei Qin; Yuan Li; Dongmei Liu; Yuzhuo Hua; Yuandong Lv; Xiaojian Zhang; Cailian Fan; Jing Yang (BMC, 2024)
Abstract Background Allii Macrostemonis Bulbus is also named Xiebai in China. It is an edible vegetable, and also a famous herb for treating coronary heart disease. Allium chinense G. Don (ACGD) and Allium macrostemon Bunge (AMB) are it botanical sources. The aim of this study was to explore the cardioprotective effects, and decipher the visual spatial distribution and absolute content of primary metabolites derived from these two herbs. Methods H9c2 cells were used to perform the hypoxia-reoxygenation (H/R)-induced myocardial injury model. Their protective effects were evaluated by apoptosis levels. Furthermore, matrix-assisted laser desorption/ionization time-of-flight tandem mass spectrometry imaging approach (MALDI-TOF MSI) was carried out to present the spatial location of primary metabolites including fatty acids, amino acids, carotenoids, and vitamins in these two Allium herbs. Multiple analytical methods were applied to perform quantitative analysis of these primary metabolites in AMB and ACGD bulbs by liquid chromatography tandem mass spectrometry (LC-MS). Results First, AMB and ACGD extracts both could increase the cell viability in H9c2 cells, and attenuate H/R-induced injury. They markedly decreased apoptosis, accompanied by activating the BCL-2/BAX pathway. Further, MALDI-TOF MSI-based relative quantification results showed several amino acids, fatty acids, carotenoids, and vitamins were largely rich in the tunics and outside scales of fresh bulbs, while some primary metabolites were abundant in their developing flower buds. Absolute quantification results displayed total contents of amino acids in ACGD bulbs were higher than those in AMB, while total contents of fatty acids and vitamins provides opposite trends in these two Allium herbs. The total contents of carotenoids and trace elements showed no significant differences between AMB and ACGD samples. Conclusions This study would be helpful to understand the myocardial injury protection effects of these two Allium herbs, and the spatial accumulation and quantitative content levels of their main nutrients. Graphical Abstract